THE POLITICAL IDENTITY OF SERBIA IN THE DISCOURSE OF MILITARY NEUTRALITY IN EUROPE (Heritage, 2025)
The dynamics of the development of contemporary geopolitical relations with the tendency to intensify the conflict between global power centers is additionally complicated by the growth and development of the foreign policy ambitions of regional powers, which strive to create a new global order. In this context, they did not reach a global consensus on maintaining world peace and security. States with significantly less political, economic and military power, i.e. weak states or peripheral states, in order to ensure their survival, must rely on their own forces or adhere to current military alliances. At a time when the number of armed conflicts is growing and affecting all parts of the world, including Europe, the question arises whether military neutrality is the safest way to defend vital national interests and the best concept for building a political identity. The paper analyzes the contemporary practices of building the identity policy of European states through strategic patterns of establishing military neutrality, as well as the specific position of Serbia in the NATO environment. Military neutral states do not only declaratively advocate for universal values ​​such as peace, freedom, equality, democracy, rule of law, but with their active policy they protect and promote the values ​​defined by international law. Identity policy is not only a proclaimed principle, but a set of values ​​that the state defends and represents in international relations through its security culture, thus becoming recognized in international relations. The conclusion is that in its foreign policy, Serbia must find effective mechanisms for implementing the concept of military neutrality through the affirmation of identity politics and strategic security culture.
Keywords: military neutrality, political identity, security, R. Serbia, Europe